Adipocyte‐Derived Anticancer Lipid Droplets. Issue 26 (13th May 2021) - Liang, Tingxizi; Wen, Di; Chen, Guojun; Chan, Amanda; Chen, Zhaowei; Li, Hongjun; Wang, Zejun; Han, Xiao; Jiang, Liping; Zhu, Jun‐Jie; Gu, Zhen
Abstract: Engineering of efficient and safe materials remains a challenge for cancer therapy. Here, the lipid droplet, an organelle in adipocytes, is demonstrated to be a controllable and biocompatible vehicle to deliver anticancer drugs. It is validated that isolated lipid droplets maintain their key physiological functions to interact with other organelles and augment the therapeutic effect of cancer photodynamic therapy by encapsulation with a lipid‐conjugated photosensitizer (Pyrolipid) through a variety of pathways, including generation of reactive oxygen species (ROS); lipid peroxidation; and endoplasmic reticulum (ER) stress. As such, the IC50 value of Pyrolipid is reduced by 6.0‐fold when loaded into the lipid droplet. Of note, in vivo results demonstrate that engineered lipid droplets induce significant inhibition of tumor growth with minimal side effects. Abstract : The lipid droplet, an organelle in adipocytes, is engineered to be a controllable, effective, and biocompatible drug delivery system for cancer therapy. It is demonstrated that the lipid droplet can augment the therapeutic performance of an encapsulated drug via several pathways, including generation of reactive oxygen species, lipid peroxidation, and endoplasmic reticulum stress, providing a promising material with clinical translation potential.